2005
DOI: 10.1097/00000542-200506000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Deprivation on Righting Reflex in the Rat Is Partially Reversed by Administration of Adenosine A1 and A2 Receptor Antagonists

Abstract: Both antagonists partially reversed the effect of sleep deprivation on anesthetic action. This result implies that deprivation-induced changes in adenosine receptor activity can alter LORR. Neither antagonist completely reversed this effect, suggesting possible non-adenosine-mediated effects of sleep deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…In in vitro studies, mefloquine has been shown to interact with a number of potential neurological targets, including neuronal calcium homeostasis, the endoplasmic reticulum calcium pump, acetylcholinesterase, blood-brain barrier P glycoproteins, glutaminergic synaptic activity, connexins, A 2 a receptors, and potassium and anion channels (6,8,16,17,21,22,24,30,44). The A 2 a receptor is a strong candidate for potential involvement, given its suspected role in sleep modulation and its potent inhibition by mefloquine (41,42,44).…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro studies, mefloquine has been shown to interact with a number of potential neurological targets, including neuronal calcium homeostasis, the endoplasmic reticulum calcium pump, acetylcholinesterase, blood-brain barrier P glycoproteins, glutaminergic synaptic activity, connexins, A 2 a receptors, and potassium and anion channels (6,8,16,17,21,22,24,30,44). The A 2 a receptor is a strong candidate for potential involvement, given its suspected role in sleep modulation and its potent inhibition by mefloquine (41,42,44).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that the majority of actions ascribed to therapeutic doses of xanthines (caffeine and theophylline) are due to their action as adenosine receptor antagonists [13]. The role of adenosine in sleep and its sedative/hypnotic activities are well known [14][15][16][17][18]. In our volunteer study noted above, we demonstrated the antagonistic actions of aminophylline on propofol sedation; these actions were assessed using both the bispectral index (BIS) and behavioral responses to verbal commands.…”
Section: Discussionmentioning
confidence: 69%
“…In rodents, loss of consciousness can be measured by the LoRR and resumption of consciousness can be analyzed by the RoRR (19,20). Fig.…”
Section: Methodsmentioning
confidence: 99%